2013
DOI: 10.1002/jso.23353
|View full text |Cite
|
Sign up to set email alerts
|

Novel focal adhesion protein kindlin‐2 promotes the invasion of gastric cancer cells through phosphorylation of integrin β1 and β3

Abstract: Kindlin-2 might promote the invasion of gastric cancer cells through enhancing proliferation and adhesion by the phosphorylation of integrin β1 and β3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 25 publications
0
33
0
1
Order By: Relevance
“…Kindlin-2 is a member of the kindlin family of focal adhesion proteins, and is involved in integrin signaling and linkage of the actin cytoskeleton to the extracellular matrix. Although few studies report on kindlin-2, it has been found to be up-regulated in breast and gastric cancer cell lines [29, 30], but down-regulated in leiomyosarcomas [31] and mesenchymal cancer cells [32]. Targeting kindlin-2 may improve drug efficacy and reduce the dose of drug required to treat prostate cancer [33].…”
Section: Discussionmentioning
confidence: 99%
“…Kindlin-2 is a member of the kindlin family of focal adhesion proteins, and is involved in integrin signaling and linkage of the actin cytoskeleton to the extracellular matrix. Although few studies report on kindlin-2, it has been found to be up-regulated in breast and gastric cancer cell lines [29, 30], but down-regulated in leiomyosarcomas [31] and mesenchymal cancer cells [32]. Targeting kindlin-2 may improve drug efficacy and reduce the dose of drug required to treat prostate cancer [33].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in esophageal SCC, kindlin-2 itself might be a target for miR-200b, resulting in decreased kindlin-2 levels and tumor cell invasion . In addition to regulation of EMT and invasion, kindlin-2 has been shown to promote cell survival through stimulation of Hedgehog signaling by inducing the expression of Loss of expression increases cell invasion EMMPRIN regulates kindlin-3 and β1 integrin expression Delyon et al, 2015 Gli1 and anti-apoptotic Bcl2 proteins (Gao et al, 2013;Gong et al, 2010;Shen et al, 2013). Kindlin-2 has also suggested to enhance genome instability, a hallmark of cancer formation, although it is not clear how this is achieved at the molecular level (Zhao et al, 2013).…”
Section: Kindlin-2 Is Involved In Multiple Diseasesmentioning
confidence: 99%
“…Kindlin-2 expression has been found to be dysregulated in several cancer types: prostate 74-77 breast 64, 78-80 , lung 65, 81 , colorectal cancer 82 , pancreas 83, 84 ovarian 85, 86 , esophageal squamous cell carcinoma 87-89 , liver 90 , brain 91 , gastric cancer 92, 93 , bladder 94 , and acute myeloid leukemia 95 . Given the association of kindlin-2 with several cancers of different origins, one can predict an important role that kindlin-2 may play in cancer pathogenesis.…”
Section: Association Of Kindlins With Cancermentioning
confidence: 99%